THE RELATIONSHIP BETWEEN INTEREST OF LEARNING AND INTERCOMMUNICATION OF PEER TOWARD MATHEMATICS LEARNING OUTCOMES IN CLASS VIII - Isna Nur Hayati; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Low learning achievement of mathematics students related to a variety of factors. The interest of learning and intercommunication of peers are two factors allegedly related to the student's mathematics learning outcomes. This research aims to know if there is a positive and significant relationship between the interest of learning and intercommunication of peers toward mathematics learning outcomes in class VIII State Junior High School 2 Gamping Sleman (SMP Negeri 2 Gamping Sleman) of odd semester academic year 2017/2018. The population in this research was all class VIII students in SMP Negeri 2 Gamping Sleman of odd semester academic year 2017/2018, which amounts to 192 students and divided into six classes. Function random sampling technique to class to take a sample class, to obtain class VIII E as a trial class and class VIII F as a research class. Data collection techniques are done with the questionnaire method and the test method. The research instruments used questionnaire interest of learning, questionnaire intercommunication of peer, and learning outcomes test. The instruments test used tests of validity, different power, and reliability testing. Analysis of instrument trials using the normality test, independent test, and linearity test. Data analysis using simple correlation analysis and multiple regression analysis. The results showed a positive and significant relationship between the interest of learning and intercommunication of peer toward mathematics learning outcomes with multiple regression equation  and the multiple correlation coefficient  is . And obtained  and , so . Donation are relatively  and , with multiple determination coefficient of and the effective contribution  and .